Pick One Intelligent Girl : Employability, Domesticity and the Gendering of Canada's Welfare State, 1939-1947 - Stephen, Jennifer Anne, 1959- (Book collections on Project MUSE., 2007)
"During the tumultuous formative years of the Canadian welfare state, many women rose through the ranks of the federal civil service to oversee the massive recruitment of Canadian women to aid in the Second World War. Ironically, it became the task of these same female mandarins to encourage women to return to the household once the war was over. Pick One Intelligent Girl reveals the elaborate psychological, economic, and managerial techniques that were used to recruit and train women for wartime military and civilian jobs, and then, at war's end, to move women out of the labour force altogether." "This engaging study not only adds to the debates about the gendered origins of Canada's welfare state, it also makes an important contribution to Canadian social history, labour and gender studies, sociology, and political science."--Jacket